2011
DOI: 10.2106/jbjs.j.00489
|View full text |Cite
|
Sign up to set email alerts
|

Career Plans of Current Orthopaedic Residents with a Focus on Sex-Based and Generational Differences

Abstract: We should continue efforts to collect workforce data and be proactive to avert or minimize the effect of impending orthopaedic workforce shortages on our patients. Given the trend toward an increasing proportion of female orthopaedists and the higher likelihood that they will reduce their work hours during portions of their career, policymakers should consider training more orthopaedists to ensure patient access to timely, quality orthopaedic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 12 publications
3
50
0
1
Order By: Relevance
“…Although the time between completion of fellowship training and sitting for the ABOS Part II examination may vary, this served as a surrogate for the number of recently trained orthopaedic oncology fellows. Similar to previous studies [8,9], we found that there was a greater number of examinees who reported orthopaedic oncology fellowship training during the second half of the study than during the first 5 years of the study. Since the first orthopaedic oncology fellowship was established in the late 1970s, there has been a slow but steady increase in the number of available fellowship positions [5,6].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the time between completion of fellowship training and sitting for the ABOS Part II examination may vary, this served as a surrogate for the number of recently trained orthopaedic oncology fellows. Similar to previous studies [8,9], we found that there was a greater number of examinees who reported orthopaedic oncology fellowship training during the second half of the study than during the first 5 years of the study. Since the first orthopaedic oncology fellowship was established in the late 1970s, there has been a slow but steady increase in the number of available fellowship positions [5,6].…”
Section: Discussionsupporting
confidence: 90%
“…Nearly 90% of today's orthopaedic residents will pursue additional subspecialty fellowship training, a number that has continued to increase with time [8,9]. Potential explanations for the recent increase in fellowship training include the desire for a focused clinical practice, angst resulting from limited exposure to techniques during residency training, market influences, and financial incentives [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…15 Similarly, a recent survey found that 13% of orthopedic residents in postgraduate year 3 or higher in the United States are women. 16 Hopefully, the increasing prevalence of female orthopedists will lead to a greater female representation among the field's leaders. The long hours and lack of family time in orthopedic leadership positions may play a role in the small number of women who serve in these positions.…”
Section: Discussionmentioning
confidence: 99%
“…This necessitates flexible training in order to accommodate maternity requirements, along with a potential rise of less-than-full-time training. Alongside sex differences, generational changes must also be considered, as you cannot assume the career longevity of current trainees will be the same as their predecessors [5].…”
Section: Current Workforce Challengesmentioning
confidence: 99%